Europe's long-term growth prospects: With and without structural reforms - Kieran McQuinn; Karl Whelan (University College Dublin, UCD School of Economics, 2015)
Even before the financial crisis of 2007/08, there were significant questions about Europe's long-term growth prospects. After a long period of catching up with US levels of labour productivity, euro area productivity growth had, from the mid-1990s onwards, fallen significantly behind. Using data for the period 1970 to 2006, McQuinn and Whelan (2008) identified declining rates of total factor productivity (TFP) growth and weaker capital accumulation as areas for concern in an European context. In updating this earlier analysis, we find that the growth prospects of the euro area have deteriorated further. With TFP growth contin- uing to fall, Europe's demographics are now also contributing to a decline in the workforce. Against this backdrop, we provide a long-term projection for euro area GDP based on unchanged policies and discuss the possible impacts of certain structural reforms including potential changes in the unemployment rate, pension reform and the successful implementation of a significant wider programme of regulatory reform that boosts TFP growth. We argue that, even with the successful adoption of these measures, the European economy is still likely to grow at a slower pace than it has in the past.
Keywords: O40; O47; O16; 330; Growth; Euro Area; Demographics; Structural Reforms